COMPARISON OF PATIENT SAFETY PERCEPTION IN PRECLINICAL AND CLINICAL STUDENTS - Yopi Simargi; Steven Alvianto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Patient safety is a global problem and patient safety education for medical students is needed to improve the quality of health services. This study aimed to determine the mean difference of perception on nine patient safety key factors between preclinical students and clinical students.Methods: This observational analytic cross-sectional study was conducted on preclinical students and clinical students at the School of Medicine and Health Sciences of Atma Jaya Catholic University of Indonesia (AJCUI) in the academic year 2019/2020, randomly drawn in each batch. The research data was collected using the Attitude to Patient Safety Questionnaire -III (APSQ-III) with 7 Likert scales. Data analysis using independent t-test.Results: From 389 students, significant mean differences of patient safety perception between preclinical students and clinical were found for five key factors: PS training received (p = 0.000), Error reporting confidence (p = 0.000), Working hours as an error cause (p = 0.000), Team functioning (p = 0.001), and Patient involvement in reducing error (p = 0.000).Conclusion: Medical students had positive perceptions of patient safety. However, there were still some significant different perceptions between clinical and preclinical students, which indicated the need for patient safety education integration in the medical education curriculum.